Houellebecq à l’encontre ou au centre de l’utopie ? Une analyse de l’ambivalence utopique dans La Possibilité d’une île - Françoise Campbell (ReS Futurae)
The relationship between the utopian genre and the work of Michel Houellebecq is as evident as it is perplexing. Torn between present and future worlds, and narrated by diverse and often antagonistic voices, Houellebecq’s narratives manifest an attraction towards other worlds. However, these texts, characterised by their cutting social critique, play upon the very possibility of imagining a better world. To better understand the critical significance of this ambivalence, this study focuses on La Possibilité d’une île and explores how Houellebecq situates himself simultaneously against and within the utopian tradition.